England's cross of gold Keynes, Churchill, and the governance of economic beliefs - Morrison, James Ashley, 1980- (Cornell studies in money., 2021)
"James Ashley Morrison's heavily archival work offers a new account of the ideas and leading actors that drove Churchill's disastrous decision to restore Britain to the gold standard following World War I. It directly challenges the conventional view that Churchill restored the gold standard because it was in the political interest of his Conservative party, because it served the economic interests of Britain's elites, and because UK institutions shielded policy-makers from the hardships it would impose upon ordinary Britons. By offering a new understanding of the clashes that led the world into the violence and chaos of the 1930s, the book also offers insights into the challenges that the 'embedded liberal' international order faces today"--